2019
DOI: 10.1002/ctpp.201800143
|View full text |Cite
|
Sign up to set email alerts
|

Equation‐of‐state studies of high‐energy‐density matter using intense ion beams at the Facility for Antiprotons and Ion Research

Abstract: This paper describes an experiment design based on numerical simulations to measure the equation‐of‐state properties of high‐energy‐density (HED) matter using intense particle beams. The simulations are performed using a 2D hydrodynamic computer code, BIG2, while the beam parameters are considered to match the Facility for Antiprotons and Ion Research beam. This study has shown that in such experiments one can generate different phases of HED lead. Similar calculations are planned for other materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…To do it, the experiments with ion beams can be used. [ 16,17 ] The temperature in these measurements can reach 50 kK, although the estimates for density have shown that it is still kept near the melting values. Besides these two types of measurements, there are several theoretical approaches that were applied to describe the shock‐wave measurements data and to construct the equation of state for a number of metals including Pb.…”
Section: Introductionmentioning
confidence: 98%
“…To do it, the experiments with ion beams can be used. [ 16,17 ] The temperature in these measurements can reach 50 kK, although the estimates for density have shown that it is still kept near the melting values. Besides these two types of measurements, there are several theoretical approaches that were applied to describe the shock‐wave measurements data and to construct the equation of state for a number of metals including Pb.…”
Section: Introductionmentioning
confidence: 98%
“…The proposed experimental program is based on theoretical studies that include detailed numerical simulations and analytic modeling, as reported in [5,6,7,8,9,10,11,12,13,14,15,16,17,18,44,20,21,22,23,24,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…This flexibility is not provided by any other generator. An experiment based on the former scheme named HIHEX (Heavy Ion Heating and Expansion) has been designed with the help of detailed numerical simulations to study the EOS properties of HED matter [43,[56][57][58]. The second scheme is employed to propose another experiment named, LAPLAS, that stand for Laboratory Planetary Science and that uses a multiple shock reflection technique that leads to a low-entropy compression of a sample material which is enclosed in a cylindrical high-Z shell.…”
Section: Introductionmentioning
confidence: 99%